2015
DOI: 10.1007/s10841-015-9764-7
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism by water mites in native and exotic Corixidae: Are mites limiting the invasion of the water boatman Trichocorixa verticalis (Fieber, 1851)?

Abstract: The water boatman Trichocorixa verticalis verticalis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Concerning the study on the preferences of water mites for the host sex, the conclusion varies in some cases. No differences in the prevalence due to host sex were sometimes recorded (Martin and Stur 2006;Robb and Forbes 2006;Fairn et al 2008;Zawal and Buczyński 2013;Sánchez et al 2015). On the contrary, female hostbiased prevalence was reported by Yasick et al (2003), Zawal (2006a), Baker et al (2008), Zawal and Daytlova (2008), Radhakrishnan et al (2010), and Kulijer et al (2012).…”
Section: Introductionmentioning
confidence: 90%
“…Concerning the study on the preferences of water mites for the host sex, the conclusion varies in some cases. No differences in the prevalence due to host sex were sometimes recorded (Martin and Stur 2006;Robb and Forbes 2006;Fairn et al 2008;Zawal and Buczyński 2013;Sánchez et al 2015). On the contrary, female hostbiased prevalence was reported by Yasick et al (2003), Zawal (2006a), Baker et al (2008), Zawal and Daytlova (2008), Radhakrishnan et al (2010), and Kulijer et al (2012).…”
Section: Introductionmentioning
confidence: 90%
“…Our results show that freshwater salinisation can influence both individual host–parasite interactions and the effects of parasites on host populations. Several previous studies have found reduced parasite success in high salinity environments (Miron et al., ; Sanchez et al., ; Stockwell et al., ), suggesting that our result of lower infection prevalence in high salinity may be a common phenomenon. For introduced or emerging parasites, reducing infection prevalence with high salinity may be desirable if the host species is under threat and able to withstand high salinity.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, biological interactions such as resource competition, predation or parasitism might also play a role in explaining the observed exclusion pattern (Reitz & Trumble ; Carbonell, Millán & Velasco ; Sánchez et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, higher rates of parasitism by water mites compared to native Sigara may limit the occurrence of T. v. verticalis in fresh waters (Sánchez et al . ).…”
Section: Discussionmentioning
confidence: 97%